Alizarin red S functionalized mesoporous silica modified glassy carbon electrode for electrochemical determination of anthracene. (1st April 2015) - Liu, Shan; Wei, Maochao; Zheng, Xiangli; Xu, Shuai; Xia, Fangquan; Zhou, Changli
Graphical abstract: Highlights: Alizarin red S-SBA15 composite was prepared and characterized. A novel sensing platform was constructed for anthracene determination. The proposed sensor exhibited high sensitivity and low detection limit for detecting anthracene. This method can be applied to the practical detection of anthracene in waste water. Abstract: In the paper, a novel and sensitive electrochemical sensor based on modification of electroactive alizarin red S functionalized mesoporous silica material SBA15 onto glassy carbon electrode (ARS-SBA15/GCE) was developed. Alizarin red S, called electrochemical probe that can selectively recognize polycyclic aromatic hydrocarbons (PAHs), as tools for the detection of tricyclic aromatic hydrocarbon anthracene. The morphology and interface property of ARS modified SBA15 (ARS-SBA15) were examined by transmission electron microscopy (TEM) and fourier transform infrared spectroscopy (FTIR). Taking advantage of the π-π stacking force between alizarin red S and anthracene, the ARS-SBA15/GCE sensor could detect anthracene quantitatively in a wide range of 1.0 pM–10.0 nM and a low detection limit of 0.5 pM (S/N = 3). Other PAHs, such as naphthalene, phenanthrene, pyrene, and benzo[a]pyrene show little interference on the detection. Consequently, a simple and sensitive electrochemical method was proposed for the determination of anthracene, which can be used to determine anthracene in waste water samples. The electrochemical method provides a general tool that complements the commonly used spectroscopic methods and immune method for the detection of PAHs.